Invited articleBoost in radiotherapy: external beam sunset, brachytherapy sunrise - Maciejewski, Bogusław (Journal of Contemporary Brachytherapy, 2009)
Radiobiological limitations for dose escalation in external radiotherapy are presented. Biological and clinical concept of brachytherapy boost to increase treatment efficacy is discussed, and different methods are compared. Oncentra Prostate 3D conformal real-time ultrasound-guided brachytherapy is presented as a solution for boost or sole therapy.